Mechanisms of graphene fabrication through plasma-induced layer-by-layer thinning. (August 2016) - Seah, Choon-Ming; Vigolo, Brigitte; Chai, Siang-Piao; Mohamed, Abdul Rahman
Abstract: Graphene is a layer of sp 2 hybridized carbon of a single-atomic thickness, which exposes most of its atoms to the surrounding medium. The properties of graphene are highly dependent on its number of layers. Currently, the synthesis of uniform graphene with a specific number of layers in a controllable way is rather hard. In this review, we present the highlights of current advances regarding utilization of various plasmas for the control of graphene thickness. The mechanisms involved in the etching phenomenon of the graphene sheet to realize the layer control are particularly analyzed and compared. A precise layer-by-layer etching could be achieved using controlled operating parameters of different kinds of plasmas applied to graphene and combined with sub-layer substrate effects. With this review, we propose a concise overview of the application of plasma as the basis of development of new approaches to obtain uniform graphene with the desired number of layers in near future.